Ariadne Konstantinou, Female Mobility and Gendered Space in Ancient Greek Myth, London:Bloomsbury Academic, 2018 - Bednarek, Bartłomiej (Polskie Towarzystwo Filologiczne, 2018)
Ariadne Konstantinou, Female Mobility and Gendered Space in Ancient Greek Myth, London: Bloomsbury Academic, 2018, 208 pp., ISBN 978-14-725-677-3, £81.00.
Keywords: censurae liborum